Deregulasi Bursa Efek Jakarta, 1987—1997 - Suparjo Rohman (Universitas Gadjah Mada, 2016)
This paper discussed about deregulations in Jakarta Stock Exchange on periods 1987-1997 that used history method, that comprise with heuristic, critic, interpretation, and historiography. The purposes about this research are to know historicalback ground and the impacts of government’s deregulations toward Jakarta Stock Exchange in 1987 until 1997. The Jakarta Stock Exchange that has activated by Soeharto’s Era have purposes to create equity distribution income. In efforts to achieve this goal, the government set up some rules about capital markets. In practice, these rules caused the Jakarta Stock Exchange experienced a decline. To solve the causeds, the government make deregulation of capital market. Deregulation aimed to eliminating overly burdensome regulation of capital markets. The Deregulation of capital markets is Paket Desember 1987, Paket Desember 1988, SK Menteri Keuangan No. 1055/KMK.013/1989 and S.K. Menteri Keuangan No. 1548/KMK.013/1990. The impact of deregulation, Jakarta Stock Exchange experienced a boom in 1987-1989. In the long-period impact, Jakarta Stock Exchange is open for foreign investors and then subjected to privatization.